Epidemiology of injuries in parkour and review literature - Giner-Gran, MA. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2020)
Parkour is an increasingly popular physical activity that continues to attract practitioners. The aim of the study is to analyze the prevalence of injuries in parkour as well as nature, anatomical zone, required procedure, place where it happened and parkour movement. The practitioners of the Community of Madrid were analyzed, with a total of 161 subjects with a minimum of 12 months experience and at least 1 time per week regular practice, using an ad hoc questionnaire. The results show an injury prevalence of 70.2%, where are more frequent: sprains (22.3%) and contusions (21.1%), lower extremities (69.9%) and upper limbs (24.7%), did not need medical tests or surgery (68.6%), park or plaza (60,9%) and street (28%), and precision jump (18.8%) and running precision jump (11.1%). %). In conclusión, the data obtained confirm that parkour is susceptible to suffer injuries, mostly sprains, in the lower extremity and are not serious.